Algebra
posted by Juri .
Simplify (2xy^2+3)((2xy^2)^2(2xy^2)(3)+(3)^2)
This reminds me of
(U+a)(U^2 aU + a^2). When mulipltiplied out, one gets a cubic equation. Do you remember the formula for factoring the sum of two cubes?
a^3+b^3= ????
Respond to this Question
Similar Questions

Algebra (new one since I put "match" (bad speller)
I have a few match problems that I can't figure out. 1.solve: 3x+5=x√7 (that's a radical sign) 2.factor: (2k+3)2(2x+3)(y2)20(y2)2 (the "2" after (2k+3) ans (y2) is suppose to be a square sign. thanks if you can help, or … 
Algebra
Factor out 8x^3y^6 + 27 One factor is 2xy^2+3. (The sum of the cube roots of the first and last terms). Use long division to compute (8x^3y^6 + 27)/(2xy^2 + 3) to get the other factor 
Math
Can 2xy  y  1 be factored out? How? about all you can do is take the common y out of the first two terms; that in itself is not much help. dont know if this is rite or not..but just a guess.. assuming 2xy  y  1 = 0 2xy  y = 1 
Calculus
Consider the equation: x^2  2xy + 4y^2 = 64 Write an expression of the slope of the curve at any point. (y^p)= y prime My work 2x  2(xy^p + y) + 8yy^p = 0 2x 2xy^p  2y + 8yy^p = 0 2xy^p + 8yy^p = 2y 2x factored out y^p and then … 
calculus
simplify 6x^42xy^4 divided by 2xy 
Algebra
I thought number 4 on this list was incorrect but didn't know how to fully explain it here is the list that I have. Please look at the following simplification of an algebraic expression. Which line contains the mistake and why? 
Algebra
Please look at the following simplification of an algebraic expression. Which line contains the mistake and why? 
precal
Use Pascal's triangle to expand the expression. (x − y)5 so I tried to work this out: (xy)^5 = [(xy)(xy)][(xy)(xy)](xy) (xy)^2 = (xy)(xy) = x^2  2xy + y^2 x^2  2xy + y^2)(x^2  2xy + y^2) = x^4 4x^3y + 6x^2y^2  4xy^3 … 
simultaneous equation
x^2+y^22xy=21 x^2+2xy8y^2=0 find x and y help me plz 
Algebra 1
Make an equation to represent the area of a square whose sides are given by the expression x + y. A. A = 2x + 2y + 2xy B. A = x2 + 2xy +y2 C. A = 2(x2 + y2) D. A = x2 + y2 I got D please correct me if wrong. Thx!